Model Pengembangan PLUG-IN SLiMS Pada Komunitas SLiMS Kudus - Zaid Abdurrahman; Thoriq Tri Prabowo (IAIN Ponorogo, 2021)
This study aims to determine the role of Kudus SLiMS Community in development of the SLiMS plug-in. Researcher uses open-source development model by Ibrahim Haddad and Brian Warner from The Linux Foundation to help researcher describing SLiMS Plug-ins development in Kudus SLiMS Community. This research uses qualitative research method. Method of data collection is using direct observation, non-structured interviews, and documentation technique. The data analysis method is using Miles and Huberman method. The result of this study is that the role of Kudus SLiMS Community in development of the SLiMS plug-in is as a source of inspiration/idea for developing a plug-in, a place for the member of the Kudus SLiMS Community to share their developed plug-ins. Based on the findings of researcher related to the following study, in the future it is necessary to do further research about the development of the SLiMS plug-ins by other local SLiMS Community as a comparison with the development of the SLiMS plug-in by the Kudus SLiMS Community. The researcher hopes that more and more similar study is carried out so that the SLiMS application developer, local SLiMS Communities, and general public get the comprehensive picture about how SLiMS as one of the open-source based applications is developed.